Síntese de fitoalexinas em sorgo e soja, controle de oídio e produção de pepino, Cv. Hokushin, por leite fermentado, mananoligossacarídeo fosforilado e Kefir - Curti, Marinelva (2010)
Demands of food free of pesticides have been improved the last years, in this context, alternative methods of pests and diseases control, are stimulated by many studies. The use of alternative products has demonstrated its ability to induce defense mechanisms of plants. Aim of this work were evaluate the influence of alternative products (Kefir grains and product of milk fermentation, both submitted to heat treatment) in the induction of phytoalexins, glyceollins and deoxyanthocyanidins, in soybean cotyledons and sorghum mesocotyls, as well as, verify the potential of its applications and use of conventional products (phosphorylated mannanoligosaccharide and acibenzolar-S-methyl) to control powdery mildew in cucumber plants and evaluate efeccts on crop yields. Results sugested that, both alternative products had ability to induce the production of phytoalexins, on soybean cotyledons and sorghum mesocotyl, like levels observed for conventional products. In the same way, soluble proteins levels in leaves of cucumber plants treated with alternative products indicated higher synthesis of proteins at 48 hours after application. Results for severity of powdery mildew on cucumber plants, treated with alternative and conventional products, suggesting, no control effects by product of milk fermentation. The ability of both alternative and conventional products, to increase cucumber fruit production, was not demonstrated in this work, perhaps differences in fruit quality. Post-harvest results suggest no significance between treatments, in relation to water loss. However, treatment with product of milk fermentation apparently provided the best aspect of fruits in post-harvest.